FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI KONSUMEN PADA PENGGUNAAN ELECTRONIC PAYMENT (SERVER BASED) - Ajang Mandariza; Lalu M Furkan; Lalu Edy Herman Mulyono (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
Electronic Cash (Server-Based) is one way to realize a cashless society in Indonesia. However, previous studies have shown that there are antecedents that influence consumers' perceptions of the use of electronic cash which then also influences consumer usage decisions. This study aims to look at the antecedents that affect the perception and usage decisions of Indonesian consumers regarding the use of electronic cash (server-based).The study was conducted by survey method and analyzed using the PLS approach. The results showed that ease of use, trust, security, self-efficacy, and social influences are antecedents that influence consumer perceptions and electronic cash (server-based) usage decisions.Keywords : Electronic Cash, Server Based, Ease of Use, Trust, Security, Self-Efficacy, Social Influences, Usefulness, Consumer’s Perception, Usage Decision.